Penerapan Pembelajaran Nahwu Shorof Menggunakan Lagu Manhaji - Ahmad Roihan Al Farizi; Alfina Nur Fadhilah; Majidatun Ahmala (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2023)
Abstrak The Raudlatul Muta'allimin Princess Islamic Boarding School is one of the Islamic boarding schools in Lamongan which combines traditional and modern ways in its learning activities. One of the learning methods used in Islamic boarding schools is the Manhaji method. The Manhaji method is a method that helps to understand the Qur'an in a gradual and structured manner, starting with having to understand the meaning of Al-Mufradat's words, then a series of languages ??in the form of changing the word science of Sharf and the sentence structure of Nahwu science. This Manhaji has a bond that combines traditional Islamic boarding schools with modern Islamic boarding schools, as well as Middle Eastern learning styles. The Manhaji method is used to increase students' understanding of Nahwu Shorof, because the Manhaji method is a method that uses songs as a learning medium that makes it easier for students to learn Nahwu Sharaf. This article aims to inform readers how the application of Nahwu Shorof learning uses songs in the Manhaji method, especially at the Raudlatul Muta'allimin Islamic Boarding School which applies this method to female students. This research approach is descriptive qualitative with data collection techniques using interviews, observation, analysis, and documentation. The data collected is the result of students' written tests when learning is carried out. The results of this research state that through this manhaji song method students learn nahwu shorof in a pleasant atmosphere and help them to memorize and practice the rules of nahwu shorof in an easier way. Keywords: Islamic boarding school, The Manhaji Method, Nahwu, Sharf, Student